(untitled) (Research, Society and Development, 2023)
Rabbit farming can be viable as an activity that generates extra income in small rural properties, since it does not require high investments for its development. The southeast region of Pará is characterized by high temperatures and relative humidity, in this context, the use of material for environmental enrichment can beneficially help the well-being of animals and contribute to minimize stress in environments with high temperatures. The present work was developed with the objective of evaluating the behavior and interaction with materials used for environmental enrichment of rabbits kept in collective pens in the climatic conditions of Southeast Pará. The experiment was carried out in the rabbit breeding sector of the Federal Rural University of Amazônia, campus Parauapebas, PA. The behavior and preference for material for environmental enrichment of four rabbits housed in a collective shed were evaluated. Data collection was carried out over three days, in the morning and afternoon at intervals of 10 minutes, totaling 18 hours of observation. The ambient temperature varied between 33°C and 26.3°C. The most frequent behavior both in the morning and in the afternoon was idleness. In the morning there was a greater interaction between the rabbits and the ceramics and in the afternoon there was a greater preference for the beaten floor, these two materials had the lowest temperatures during the experiment. It is concluded that environmental enrichment can be a strategy to reduce stress and favor thermal heat exchange in rabbit rearing kept at high temperatures.